Role of Oryctes elegans (Coleoptera: Scarabaeidae) as a vector of Fusarium proliferatum, the pathogen of Fusarium leaf wilt disease of date palm in Khuzestan province - Hoorizad ghaedi; F. Kocheili; M. latifian; reza farrokhinejad (نامه انجمن حشره‌شناسی ایران, 2020)
Oryctes elegans Perll is one of the most important pests of date palm trees. The present study was done to determine the probable role of this pest as a vector of Fusarium wilt disease in date orchards of Khuzestan province. Leaf wilt disease is one of the important diseases observed in date orchards of Khuzestan. Sampling was carried out from 24 date orchards in Abadan, Khorramshahr and Shadegan, which showed simultaneous infestation by O. elegans and fungal leaf wilt diseases. The collected samples included larvae and beetles of the date palm borer, leaves, petioles and fruit bunches of the tress. Fusarium proliferatum Matsush was isolated from collected samples with different percentages. To determine the disease transferring ability of the beetles, the experiments were carried out based on randomized complete design experiment with factorial test. Four densities; 3, 5, 7 and 9 of the beetles and four concentrations of the fungal suspensions 5×103, 5×104, 5×105 and 5×106 spores per ml were used. The frequency of isolated fungi from the insect specimens and plant materials confirmed transmission of fungus by the date palm borer. The results showed a positive and significant correlation between infested trees with Fusarium wilt disease and date palm borer. The pathogenicity test showed that insects in all four densities and all four concentrations were able to transfer the fungus and disease and in the densities of 7 beetles with 5×106 spores per ml and 9 beetles with 5×105 and 5×106 spores per ml caused drying of offshoots.